2018
DOI: 10.3389/fmicb.2018.01589
|View full text |Cite
|
Sign up to set email alerts
|

Diel Patterns of Variable Fluorescence and Carbon Fixation of Picocyanobacteria Prochlorococcus-Dominated Phytoplankton in the South China Sea Basin

Abstract: The various photosynthetic apparatus and light utilization strategies of phytoplankton are among the critical factors that regulate the distribution of phytoplankton and primary productivity in the ocean. Active chlorophyll fluorescence has been a powerful technique for assessing the nutritional status of phytoplankton by studying the dynamics of photosynthesis. Further studies of the energetic stoichiometry between light absorption and carbon fixation have enhanced understanding of the ways phytoplankton adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 79 publications
6
28
0
Order By: Relevance
“…We similarly recently reported that variance of K C , derived from parallel measures of FRRf-derived ETRs and C-uptake rates, could be generally explained by patterns in light availability (Zhu et al, 2016), but importantly was much improved when considering differences in phytoplankton size structures (Zhu et al, 2017). In fact, changes in predominant species within phytoplankton communities appears to be a factor increasingly important in explaining patterns of K C (e.g., Kulk et al, 2018;Xie et al, 2018), likely reflecting selection of taxa by environmental factors that are not specifically measured as part of the assessment exercise of interest (see Hughes et al, 2018a). Patterns of K C variability over space and time therefore remain problematic to fully resolve.…”
Section: Introductionmentioning
confidence: 89%
“…We similarly recently reported that variance of K C , derived from parallel measures of FRRf-derived ETRs and C-uptake rates, could be generally explained by patterns in light availability (Zhu et al, 2016), but importantly was much improved when considering differences in phytoplankton size structures (Zhu et al, 2017). In fact, changes in predominant species within phytoplankton communities appears to be a factor increasingly important in explaining patterns of K C (e.g., Kulk et al, 2018;Xie et al, 2018), likely reflecting selection of taxa by environmental factors that are not specifically measured as part of the assessment exercise of interest (see Hughes et al, 2018a). Patterns of K C variability over space and time therefore remain problematic to fully resolve.…”
Section: Introductionmentioning
confidence: 89%
“…The PSII operating efficiency (F q ′/F v ′) quantified the fraction of functional RCII and accounted for the extent of photochemical quenching/(energy conversion) by PSII (i.e., the efficiency of charge separation in RCII) ( Suggett et al, 2003 ; Melrose et al, 2006 ). NPQ at given light level was derived from normalized Stern–Volmer quenching coefficient, defined as NPQ NSV [NPQ NSV = F o ′/F v ′, where F o ′ represented the minimum F yield in the presence of NPQ NSV , was estimated as F o ′ = F o /(F v /F m + F o /F m ′)] ( Müller et al, 2001 ; Moore et al, 2003 ; Xie et al, 2018 ; Wei et al, 2019b ).…”
Section: Methodsmentioning
confidence: 99%
“…Our FRRF measurement protocol allowed for reliable estimation of σ PSII ′ in the existence of NPQ NSV . The instantaneous RCII normalized ETR RCII (mol e – mol RCII –1 s –1 ) for each light level was calculated as the product of PAR (E, μmol quanta m –2 s –1 ), σ PSII ′ at E, F q ′/F v ′ and the constant value (6.022 × 10 –3 ) for converting μmol quanta to quanta and Å 2 (10 –20 m 2 ) to m 2 according to biophysical sigma-based algorithm ( Suggett et al, 2003 ; Schuback et al, 2015 ; Xie et al, 2018 ):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…() proposed another approach to obtain a reliable CHEMTAX result, and in the present study, we followed a modified procedure (Xie et al . ) as follows. With the average (Avg ), maximum ( Max ), and minimum ( Min ) seed ratios in Table , we randomly generated 60 seed ratio matrices with the equation SR = Avg + D × R , where R is the random number between −1 and 1, and D is Max − Avg or Avg − Min depending on whether R is positive or negative.…”
Section: Methodsmentioning
confidence: 99%